La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Situer les femmes dans l'Electronic dance music culture (EDMC) à Montréal, entre 1950 et 1955 : premier survol - Van Vliet, Kiersten (Les Cahiers de la Société québécoise de recherche en musique, 2021)

On feeling mighty real: devenir gay à Montréal pendant l’ère disco dans Funkytown, de Daniel Roby - Foerster, Maxime (Contemporary French Civilization, 2018)
Our catalogue of journals

Nightclubbing: Montréal’s Lime Light - Pemberton, Rollie (Red Bull Music Academy, 2016)
The Lime Light and its innovative DJ Robert Ouimet made Montreal a disco city during the ’70s. This is the club's story.

DJ Mini and Montreal’s Vulgar Dance Music - Madden, David (Dancecult, 2016)
This article advances claims about Montreal’s electronic dance music scene through mapping the career of one of the key actors who shaped the electroclash scene from the early 2000s onwards—music producer/DJ Mini (née Evelyne Drouin). By way of detailing the career of DJ Mini, this text attempts to add to the queer musical narratives currently emerging from music scene analyses. Counter to the experiences of many women DJs and musicians participating in heterosexual and male-dominated music scenes, Drouin received extensive mentoring and support from various informal queer social networks spread throughout the circuits of the city. Not only did she gain access to a local production network of equipment and skill sharing, Drouin was also given access to spaces where she was able to develop production skills on her own time and at her own pace. DJ Mini’s story offers a telling case for the ways in which the politics of access—institutional, social, technological—remain central to the vitality and inclusivity of local music scenes.

Sky's the Limit: The Operations, Renovations and Implications of a Montréal Gay Bar - Allan, James (Université McGill, 1997)
"A burgeoning mega-club in the heart of Montreal's gay village, Sky embodies many forces active in gay club cultures and villages across North America at the end of the twentieth century. This project documents the daily operations of Sky--as a complex architectural site, a complicated set of managerial practices, and a popular space in Montreal's Village--and outlines the theoretical implications of such an establishment for both the gay community and for club culture more generally. A large entertainment complex currently undergoing a major expansion, Sky cannot be theorized as either a wholly oppressive or completely liberatory development. Although Sky presents some of the advantages of a mega-club for the gay community--increased diversity, accessibility and community--it also highlights the disadvantages in the development of such establishments: concentration of ownership, the removal of a gay presence from city streets, and the promotion of certain gay identities and cultures over others."

Music and Dance Culture in Montreal’s Gay Village 1980 to 1995 - Van Vliet, Kiersten (Université McGill)